The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2017
DOI: 10.1590/1413-785220172502169053
|View full text |Cite
|
Sign up to set email alerts
|

Negative-Pressure Wound Therapy in the Treatment of Complex Injuries After Total Knee Arthroplasty

Abstract: Objective: To present an experience with negative-pressure wound therapy (NPWT) in the treatment of surgical wounds in patients treated for infections after total knee arthroplasty (TKA) with or without dehiscence and prophylaxis in wounds considered at risk of healing problems. Methods: We prospectively evaluated patients with TKA infection with or without surgical wound dehiscence and patients with risk factors for infection or surgical wound complications treated with Pico(r) device for NPWT in addition to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
2
2

Relationship

4
6

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 30 publications
0
5
0
Order By: Relevance
“…15 Ene et al conducted a study with infected knee prosthesis and obtained good results (no wound dehiscence and complications) with the use of NPWT. 16 In a series of 10 cases of complex lesions of the knee, Helito et al demonstrated promising results in the healing of wounds and no complications with the use of NPWT. 17 …”
Section: Discussionmentioning
confidence: 99%
“…15 Ene et al conducted a study with infected knee prosthesis and obtained good results (no wound dehiscence and complications) with the use of NPWT. 16 In a series of 10 cases of complex lesions of the knee, Helito et al demonstrated promising results in the healing of wounds and no complications with the use of NPWT. 17 …”
Section: Discussionmentioning
confidence: 99%
“…In addition, as an alternative to traditional dressings, negative-pressure wound therapy (NPWT) has been used to effectively treat open wounds in various situations [35,36]. Recently, there is increasing evidence that closed incisional NPWT (ciNPWT) can potentially reduce the risk of surgical site infection, wound complications, reoperation, and decreased length of hospitalization in patients with TKA [37][38][39]. Although we did not use this kind of ciNPWT in our study, it might be a better choice when we encounter severe wound complications in the future.…”
Section: Discussionmentioning
confidence: 99%
“…One of the recent alternatives that has been used to improve wound healing after TKA and to minimize wound complications and the incidence of infection is the use of negative-pressure therapy [ 14 , 15 ]. This type of therapy has been used successfully in several fields of medicine, such as plastic surgery, colorectal surgery and caesarean, and has achieved excellent results in the orthopaedic field, especially in cases of open fractures or open wounds [ 16 – 18 ].…”
Section: Introductionmentioning
confidence: 99%